LIVER DYSFUNCTION IN DENGUE INFECTION, AN ANALYSIS OF THE PREVIOUSLY PUBLISHED THAI CASES - Wiwanitkit, Viroj (Journal of Ayub Medical College Abbottabad, 2007)
Background: Dengue infection is a major vector-borne disease. The classical sings and symptoms of this infection include high fever, violent headache, chill and rash. However, there are a number of atypical forms of dengue infection including those presented with liver dysfunction. However, there are only a few reports concerning the liver dysfunction among the patients with dengue infections. Methods: Here, the author presents a summative study on the liver dysfunction and its clinical correlation among Thai patients in the previous studies. A literature review on the prospective studies concerning liver function and dengue infection in Thailand was performed. Results: According to this study, there are 4 reports included covering 191 Thai pediatric patients with dengue infection. The overall rate of liver dysfunction among 191 subjects is 34.6 % (66/191). The rate of liver dysfunction among the patients without shock (36/120) is not significant different from those with shock. The rate of liver dysfunction in this study is considerable high, similar to the previous reports from other developing Asian countries. In addition, about 8 % (5/66) the patients with liver dysfunction developed hepatic encephalopathy. Conclusions: This can imply the importance of detection of abnormal high transaminase enzyme among the patients with dengue infection since the consequently developed hepatic encephalopathy can be expected. Key words: Dengue, Liver, Dysfunction